European Journal of Applied Physiology and Occupational Physiology (European Journal of Applied Physiology, 2005)
Internet-Version of the European Journal of Applied Physiology ans Occupational Physiology with contents and summaries of the articles. Homepage des European Journal of Applied Physiology and Occupational Physiology mit Inhaltsverzeichnissen ab dem Jahrgang 1996 und Zugang zu den einzelnen Artikeln (Abstracts und Volltexte als PDF-Files)